Letter from the Metal Bank and Metallurgical Society to Max Bredig - Metallbank und Metallurgische Gesellschaft (1926)
Max Bredig (1902-1977) receives a letter from the Metal Bank and Metallurgical Society informing him that a position at the North German Refinery, for which he expressed interested, has been relocated and that his application will not be considered.
Keywords: Bredig, Max Albert, 1902-1977; Chemistry; Applications for positions